The Shape of the First Metatarsal Head and its Association with its Pronation Angle and the Presence of Sesamoid-Metatarsal Joint Osteoarthritis. Issue 4 (22nd October 2020) - Ono, Yoshimasa; Yamaguchi, Satoshi; Kimura, Seiji
Category: Bunion Introduction/Purpose: The rounded shape of the first metatarsal head's lateral edge on the dorsoplantar radiograph of the foot is used as a qualitative evaluation of the first metatarsal pronation in hallux valgus feet. However, the relationship between the rounded shape and the metatarsal pronation angle of the first metatarsal has not been examined in detail. Furthermore, hallux valgus often accompanies osteoarthritis in the sesamoid-metatarsal joint. Deformation of the metatarsal head by osteophytes on the lateral edge of the lateral sesamoid facet may affect the rounded shape. The purpose of this study was to evaluate the associations of the shape of the first metatarsal head with (1) the presence of osteoarthritis in the sesamoid-metatarsal joint and (2) the pronation angle of the first metatarsal head. Methods: Patients were prospectively recruited between December 2016 and March 2017. Patients with a history of previous foot and ankle surgery or destruction of the head due to rheumatoid arthritis were excluded. A total of 121 patients, with the mean age of 61 years, underwent weight-bearing dorsoplantar, lateral, and first metatarsal axial radiographs. The shape of the first metatarsal head's lateral edge was classified as either rounded, intermediate, or angular in shape in the dorsoplantar view. The presence of osteoarthritis in the sesamoid-metatarsal joint and the pronation angle of the first metatarsal head were assessed in the first metatarsal axial view. Other variables that could affect the first metatarsal shape, including the lateral first metatarsal inclination angle, were also assessed. Univariate and multivariate analyses were performed to determine the associations of the rounded shape of the first metatarsal with the pronation angle and sesamoid-metatarsal joint osteoarthritis. Results: Of 121 feet, 31, 41, and 49 feet had rounded, intermediate, and angular metatarsal heads, respectively. Sesamoid- metatarsal joint osteoarthritis was evident in 49 (40%) feet. The mean hallux valgus and first metatarsal pronation angle was 23° and 9°, respectively. The prevalence of sesamoid-metatarsal osteoarthritis was significantly higher (24 (77%), 11 (27%), and 14 (29%) for rounded, intermediate, and angular, respectively, P < .001) in feet with a rounded metatarsal head. Furthermore, the metatarsal pronation angle was significantly larger (14°, 8°, and 4° for rounded, intermediate, and angular, respectively, P < .001). These associations were also significant in the multiple regression analysis. Conclusion: A rounded metatarsal head was associated with a higher prevalence of osteoarthritis within the sesamoid-metatarsal joint, as well as a larger first metatarsal head pronation angle. A negative round sign can be used as a simple indicator of an effective correction to the first metatarsal pronation angle during hallux valgus surgery. However, in feet with sesamoid-metatarsal osteoarthritis, surgeons will need to be cautious as overcorrection may occur.